2013
DOI: 10.1063/1.4834336
|View full text |Cite
|
Sign up to set email alerts
|

Spin and orbital magnetism of coinage metal trimers (Cu3, Ag3, Au3): A relativistic density functional theory study

Abstract: We have demonstrated electronic structure and magnetic properties of Cu3, Ag3 and Au3 trimers using a full potential local orbital method in the framework of relativistic density functional theory. We have also shown that the non-relativistic generalized gradient approximation for the exchange-correlation energy functional gives reliable magnetic properties in coinage metal trimers compared to experiment. In addition we have indicated that the spin-orbit coupling changes the structure and magnetic properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The magnetic moments obtained by Datta and co-workers are a bit lower, μ­(Co 10 ) = 18 μ B and μ­(Co 11 ) = 21 μ B , as well as those obtained by Ma et al, μ­(Co 10 ) = 20 μ B , and μ­(Co 11 ) = 21 μ B . The pure Ag N clusters show the expected odd/even effect, having magnetic moments of 1 μ B and 0 μ B for odd and even N , respectively, in agreement with previous works. , The reason is that each Ag atom contributes with an s electron to the electronic cloud, so Ag N clusters with odd and even N have odd and even numbers of electrons, respectively. However, our main purpose in this section is to study the changes of the magnetic moment as the concentration varies in each N family.…”
Section: Magnetic Momentssupporting
confidence: 90%
“…The magnetic moments obtained by Datta and co-workers are a bit lower, μ­(Co 10 ) = 18 μ B and μ­(Co 11 ) = 21 μ B , as well as those obtained by Ma et al, μ­(Co 10 ) = 20 μ B , and μ­(Co 11 ) = 21 μ B . The pure Ag N clusters show the expected odd/even effect, having magnetic moments of 1 μ B and 0 μ B for odd and even N , respectively, in agreement with previous works. , The reason is that each Ag atom contributes with an s electron to the electronic cloud, so Ag N clusters with odd and even N have odd and even numbers of electrons, respectively. However, our main purpose in this section is to study the changes of the magnetic moment as the concentration varies in each N family.…”
Section: Magnetic Momentssupporting
confidence: 90%
“…It is then clear that performing calculations accurately in both ranges is extremely important. However, although several theoretical works based on DFT have studied the structure of small copper clusters [16,21,22,[30][31][32][33][34][35][36][37][38][39][40][41], to the best of our knowledge, no previous work has included the Hubbard U correction and van der Waals (vdW) dispersion forces simultaneously within a spin-polarized treatment (SGGA + vdW + U for short). By the end, we hope to convey the message that this level of treatment is indeed relevant, with important implications for future studies involving interactions between supported Cu clusters and molecules, where adsorbate-metal hybridization interaction, as well as physisorption governed by dispersion forces, are frequently present.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of Cu N cluster (N = 1-4) nanoparticles with ChCl:Urea deep eutectic solvent was studied by Ghenaatian and coworkers in 2021 [12], whereas the stability of Cu N clusters (N = 1-4) adsorbed on CuAlO 2 surfaces was studied using atomic thermodynamics by Wang and coworkers in 2022 [14]. The frequent use of these sizes of Cu N clusters motivated us to review the structures reported as stable for small copper clusters in vacuum, finding large differences between the results reported in previous works, despite the fact that some of them used the same level of theory [16,21,22,[30][31][32][33][34][35][36][37][38][39][40][41]. These differences further motivated us to carry out a study on the stability of small copper clusters, considering the frequently used cluster sizes (3-6 atoms), where the greatest discrepancies occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spin-orbit coupling is expected to be important. There exist theoretical studies regarding spin-orbit coupling effect using effective core potentials or plane-wave basis sets [13][14][15][16][17][18][19]. These studies mainly focused on the spin-orbit coupling effect on the highest-occupied lowest-unoccupied (HOMO-LUMO) energy gaps, geometries, binding energies per atom and optical absorption of gold clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Rusakov et al [16] have used two-component relativistic density functional theory with accurate small-core shape-consistent relativistic pseudopotentials and spin-orbit corrections to refine the isomerization energy profile of Au3 computed by spin-orbit free coupled cluster methods. The noble metal trimers, Au3, Ag3 and Cu3, have also been investigated applying four-component Kohn-Sham-Dirac equation in the framework of relativistic density functional theory [17].…”
Section: Introductionmentioning
confidence: 99%